Identification of circular RNAs with host gene-independent expression in human model systems for cardiac differentiation and disease. (August 2017) - Siede, D.; Rapti, K.; Gorska, A.A.; Katus, H.A.; Altmüller, J.; Boeckel, J.N.; Meder, B.; Maack, C.; Völkers, M.; Müller, O.J.; Backs, J.; Dieterich, C.
Abstract: Aims: Cardiovascular disease, one of the most common causes of death in western populations, is characterized by changes in RNA splicing and expression. Circular RNAs (circRNA) originate from back-splicing events, which link a downstream 5′ splice site to an upstream 3′ splice site. Several back-splicing junctions (BSJ) have been described in heart biopsies from human, rat and mouse hearts (Werfel et al., 2016; Jakobi et al., 2016 ). Here, we use human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CMs) to identify circRNA and host gene dynamics in cardiac development and disease. In parallel, we explore candidate interactions of selected homologs in mouse and rat via RIP-seq experiments. Methods and Results: Deep RNA sequencing of cardiomyocyte development and β-adrenergic stimulation uncovered 4518 circRNAs. The set of circular RNA host genes is enriched for chromatin modifiers and GTPase activity regulators. RNA-seq and qRT-PCR data showed that circular RNA expression is highly dynamic in the hiPSC-CM model with 320 circRNAs showing significant expression changes. Intriguingly, 82 circRNAs are independently regulated to their host genes. We validated the same circRNA dynamics for circRNAs from ATXN10, CHD7, DNAJC6 and SLC8A1 in biopsy material from human dilated cardiomyopathy (DCM) and control patients. Finally, we could show that rodent homologs of circMYOD, circSLC8A1, circATXN7 and circPHF21A interact with either the ribosome or Argonaute2 protein complexes. Conclusion: CircRNAs are dynamically expressed in a hiPSC-CM model of cardiac development and stress response. Some circRNAs show similar, host-gene independent expression dynamics in patient samples and may interact with the ribosome and RISC complex. In summary, the hiPSC-CM model uncovered a new signature of potentially disease relevant circRNAs which may serve as novel therapeutic targets. Highlights: Circular RNA Expression Patterns during human iPSC differentiation towards cardiac myocytes Comparison of differentiation time course with β-adrenergic Stimulation of hiPSC circular RNA expression. Host-gene independent regulation of circular RNAs provides an additional layer of complexity. Qualitative and quantitative comparison to human heart samples Mouse and rat homologs interact with ribosome and Argonaute 2 protein complexes.